Estimation of Some Physical and Chemical Properties and Some Heavy Elements in Lake Habbaniyah in Anbar Governorate - AL-Duleimi, Majeed Mahmoud; Jabar, Reidh A. Abdul (Journal of Ecohumanism, 2024)
The current study focused on impact of heavy elements in Lake Habbaniyah, which is within Anbar Governorate. Samples were collected from six stations. Samples were collected during the period from November 2022 to October 2023 to measure some physical and chemical properties including salinity and pH.. And studying some heavy elements, namely (lead, cadmium, chromium, zinc, copper). The results showed that the air temperature reached a maximum of (36) degrees Celsius, while the water temperature reached a maximum of (32) degrees Celsius, and the Electrical Conductivity values as maximum (2176) microcemns/cm, exceeding the permissible limits, while the salinity was also higher than permissible by (1.392) g/L, and the pH values ranged (8.5). As for the heavy Matels, the values of lead, cadmium and chromium were outside the permissible limits, which are (0.1054), (0.1280), and (0.1844) mg/L, respectively. As for the rest of the elements such as Zn and pb, recording (0.0227-0.2125), (0.0710-0.1096) mg/L, respectively.